Exploring clinical educators' perceptions of role modeling after participating in a role modeling educational program. (3rd April 2021) - Mohammadi, Elaheh; Mortaz Hejri, Sara; Sohrabpour, Amir Ali; Mirzazadeh, Azim; Shahsavari, Hooman
Abstract: Introduction: Role modeling significantly affects medical students' values, attitudes, and professional behaviors. Role modeling is a complex and multidimensional process that necessitates accurate perception and adequate knowledge and skills. However, most clinical educators do not have adequate awareness and knowledge about the positive and negative effects of role modeling. We aimed to explore clinical educators' perceptions of role modeling after participating in a role modeling educational program. Methods: This qualitative study was conducted on eighteen clinical educators who were voluntarily participated in a three-month role modeling educational program. Data were collected using reflection paper writing and were analyzed through conventional content analysis. Results: Data analysis resulted in the development of three main categories, namely closer attention to role modeling and effort for its promotion, deliberate effort to display role modeling, and creating a positive environment to increase the effectiveness of role modeling. Conclusions: Clinical educators have limited role modeling knowledge and skills, and hence, educational programs are required to improve their role modeling knowledge, attitudes, and skills. Role modeling educational programs should aim at developing educators' awareness and knowledge about role modeling, develop their reflection and self-control abilities, and sensitize them to the importance of deliberate use of role modeling.